Design and development of a nozzle-free electrospinning device for the high-throughput production of biomaterial nanofibers. (June 2021) - Waqas, Muhammad; Keirouz, Antonios; Sanira Putri, Maria Kana; Fazal, Faraz; Diaz Sanchez, Francisco Javier; Ray, Dipa; Koutsos, Vasileios; Radacsi, Norbert
Abstract: This technical note provides a step-by-step guide for the design and construction of a temperature-controlled nozzle-free electrospinning device. The equipment uses a rotating mandrel partially immersed within a polymer solution to produce fibers in an upward motion by inducing the formation of multiple Taylor cones and subsequently multi-jetting out of an electrified open surface. Free-surface electrospinning can overcome limitations and drawbacks associated with single and multi-nozzle spinneret configurations, such as low yield, limited production capacity, nonuniform electric field distribution, and clogging. Most importantly, this lab-scaled high-throughput device can provide an alternative economical route for needleless electrospinning research, in contrast to the high costs associated with industrially available upscaling equipment. Among the device's technical specifications, a key feature is a cryo-collector mandrel, capable of collecting fibers in sub-zero temperatures, which can induce ultra-porous nanostructures, wider pores, and subsequent in-depth penetration of cells. A multi-channel gas chamber allows the conditioning of the atmosphere, temperature, and airflow, while the chamber's design averts user exposure to the high-voltage components. All the Computer-Aided Design (CAD) files and point-by-point assembly instructions, along with a list of the materials used, are provided. Highlights: A step-by-step guide for the design and development of a cost-effective, high-throughput free-surface electrospinning device. The nozzle-free electrospinning device is capable of producing fibres in the micro/nanoscale. Random and aligned nanofibres mats can be produced at low and high revolution of collector respectively. Cryo-electrospinning is feasible through a special cylinder collector assembly, which can significantly increase the pore size and porosity of the developed nanofibrous scaffolds. Three variants of the spinneret assembly; a cylinder, a ball, and a spiral coil can accommodate different solution volumes and large-scale production of nanofibres, as the free-surface electrode has no clogging issues, and it allows the formation of multiple Taylor cones throughout its surface. A multi-channel gas chamber allows the conditioning of the atmosphere, temperature, and airflow, which has a direct effect in adjusting the solvent evaporation rate. The design of the chamber ensures that there is no exposure of the user to the high-voltage components.